Cdon is essential for organ left-right patterning by regulating dorsal forerunner cells clustering and Kupffer’s vesicle morphogenesis - Deng, Zhilin; Ran, Qin; Chang, Wenqi; Li, Chengni; Li, Botong; Huang, Shuying; Huang, Jingtong; Zhang, Ke; Li, Yuanyuan; Liu, Xingdong; Liang, Yundan; Guo, Zhenhua; et al. (Frontiers in Cell and Developmental Biology, 2024)
Cdon and boc are members of the cell adhesion molecule subfamily III Ig/fibronectin. Although they have been reported to be involved in muscle and neural development at late developmental stage, their early roles in embryonic development remain unknown. Here, we discovered that in zebrafish, cdon, but not boc, is expressed in dorsal forerunner cells (DFCs) and the epithelium of Kupffer's vesicle (KV), suggesting a potential role for cdon in organ left-right (LR) patterning. Further data showed that liver and heart LR patterning were disrupted in cdon morphants and cdon mutants. Mechanistically, we found that loss of cdon function led to defect in DFCs clustering , reduced KV lumen, and defective cilia, resulting in randomized Nodal/spaw signaling and subsequent organ LR patterning defects. Additionally, predominant distribution of a cdon morpholino (MO) in DFCs caused defects in DFC clustering, KV morphogenesis, cilia number/length, Nodal/spaw signaling, and organ LR asymmetry, similar to those observed in cdon morphants and cdon-/- embryos, indicating a cell-autonomous role for cdon in regulating KV formation during LR patterning. In conclusion, our data demonstrate that during gastrulation and early somitogenesis, cdon is essential for proper DFC clustering, KV formation, and normal cilia, thereby playing a critical role in establishing organ LR asymmetry.